Employing the behavioral integration of the top management team (TMTBI) in enhancing the strategic flexibility of organizations, "an applied study on a sample of top management employees in Algerian public banks - mehdaoui, Moataz bellah Ben amer; messahel, abderrahman; Kafi, mimoun (Journal of Excellence for Economics and Management Research, 2023)
This study aims to determine the effect of the dimensions of behavioral integration of the top management team on the dimensions of strategic flexibility combined. To study the reality of this effect, a random sample consisting of 87 executives of top management distributed to a group of Algerian public banks in each of Province of Al-Bayadh, Tiaret and Laghouat was selected, relying on the questionnaire as a tool for data collection and processing with a set of appropriate statistical methods using the Spssv26, it was found that there is a strong statistically significant effect of the dimensions of behavioral integration of the top management team in enhancing strategic flexibility in Algerian public banks, and therefore the study recommends that the banking sector should update its philosophy to harmonize contemporary administrative issues, especially with regard to organizational behavior.